Tests of a dual-readout fiber calorimeter with SiPM light sensors - Antonello, Maddalena; Caccia, M.; Cascella, M.; Dunser, M.; Ferrari, R.; Franchino, Silvia; Gaudio, G.; Hall, K.; Hauptman, J.; Jo, H.; Kang, K.; Kim, B.; et al. (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2018)
In this paper, we describe the first tests of a dual-readout fiber calorimeter in which silicon photomultipliers are used to sense the (scintillation and Čerenkov) light signals. The main challenge in this detector is implementing a design that minimizes the optical crosstalk between the two types of fibers, which are located very close to each other and carry light signals that differ in intensity by about a factor of 60. The experimental data, which were obtained with beams of high-energy electrons and muons as well as in lab tests, illustrate to what extent this challenge was met. The Čerenkov light yield, a limiting factor for the energy resolution of this type of calorimeter, was measured to be about twice that of the previously tested configurations based on photomultiplier tubes. The lateral profiles of electromagnetic showers were measured on a scale of millimeters from the shower axis and significant differences were found between the profiles measured with the scintillating and the Čerenkov fibers.